[Western Australia 1:50 000 photomosaic series]. 2229 IV,. Tonebridge - Western Australia. Department of Lands and Surveys (Perth, W.A. : Dept. of Lands and Surveys, 1981)
An uncontrolled mosaic compiled in the format of the National topographic map series.
Keywords: Tonebridge (W.A.) -- Maps; Remote-sensing maps